PROBLEMATIKA PERLINDUNGAN HAK CIPTA KARYA FOTOGRAFI DI MEDIA SOSIAL BERDASAKAN UNDANG-UNDANG NOMOR 28 TAHUN 2014 TENTANG HAK CIPTA - Muhammad Alvi Sadewo; Munawar Kholil (Fakultas Hukum Universitas Sebelas Maret, 2021)
Abstract Article is intended to determine the problematic implementation of the protection of the legal rights of copyright works of photography in the media of social method of research that is used in the writing of the law this is a method of study law empirical or non-doctrinal research (social legal research) the use of materials of law consists of primary data in the form of interviews and secondary data in the form of a literature study . Data processed by the techniques of analysis of data qualitatively using the method of analysis interactive . The results of the study that the problems of implementation of the protection of the legal rights of copyright works of photography in the media of social among other weaknesses in principle deklartif , difficulty in doing the proof of ownership rights of copyright Media social as the implications of the advancement of technology information that led to increased severity of the protection of the rights of copyright on a media social , the granting sanction violations of the rights of copyright that does not cause the effect deterrent ownership of the account media social more than one also becomes one of the causes of widespread violations of the rights of copyright in media social . the lack of protection of the rights of copyright in media social which one of them on the terms and ketentuanya , lack of enforcement of laws regarding perlanggaran Rights Reserved in media social , and the latter the lack of understanding of the creators of the rights of copyright both in the literal as well as regulatory legislation which set of rights copyright Keywords: Copyright; Photography; protection; Social media Abstrak Artikel ini bertujuan untuk mengetahui problematika pelaksanaan perlindungan hukum hak cipta karya fotografi di media sosial Metode penelitian yang digunakan dalam penulisan hukum ini adalah metode penelitian hukum empiris atau non-doctrinal research (social legal research) yang menggunakan bahan hukum terdiri dari data primer berupa wawancara dan data sekunder berupaa studi kepustakaan. Data diolah dengan Teknik analisis data kualitatif menggunakan metode analisis interaktif. Hasil penelitian bahwa problematika pelaksanaan perlindungan hukum hak cipta karya fotografi di media sosial antara lain kelemahan pada prinsip deklartif, kesulitan dalam melakukan pembuktian kepemilikan hak cipta, media sosial sebagai implikasi dari kemajuan teknologi informasi yang menyebabkan bertambah parahnya perlindungan hak cipta pada media sosial, adanya pemberian sanksi pelanggaran hak cipta yang tidak menimbulkan efek jera kepemilikan akun media sosial lebih dari satu juga menjadi salah satu penyebab maraknya pelanggaran hak cipta di media sosial. lemahnya perlindungan hak cipta di media sosial yang salah satunya pada syarat dan ketentuanya, kurangnya penegakan hokum mengenai perlanggaran Hak Cipta di media sosial, dan yang terakhir yakni rendahnya pemahaman para pencipta mengenai hak cipta baik secara harfiah dan juga peraturan perundang-undangan yang mengatur tentang hak cipta. Kata Kunci : Hak Cipta; Karya Fotografi; perlindungan; Media sosial